Back-end porting of FT_MX based on LLVM compilation architecture - Deng Ping; Zhu Xiaolong; Sun Haiyan; Ren Yi (MATEC Web of Conferences, 2021)
The processor FT_MX is a high-performance chip independently developed by the National University of Defense Technology, with an innovative architecture and instruction set. LLVM architecture is a widely used and efficient open source compiler framework initiated by the University of Illinois. This paper introduces the basic architecture and functions of LLVM, analyzes the back-end migration mechanism of the architecture in detail, and gives the specific process of implementing FT_MX back-end migration, and realizes the support of LLVM architecture to the back-end of FT_MX processor.